A study on outcome of intubation in Emergency Department, Hospital Universiti Sains Malaysia. - Mohd Alip, Rabiha (2011)
Introduction. In Malaysia, Emergency Medicine is a new specialty without any less important role in health care delivery. Universiti Sains Malaysia is the first university in Malaysia offering postgraduate study in Emergency Medicine. Aims of this study were to observe the outcome of intubations, the success rate of intubations, method of intubations , presence of difficult airway and complication after intubations in emergency department, Hospital Universiti Sains Malaysia (HUSM). Objectives: To determine the success rate of intubations, method of airway management, predictors of difficult intubation and complications of intubation performed by airway personal in emergency department, Hospital Universiti Sains Malaysia (HUSM). Methodology: This was a cross sectional observational study done in emergency department, Hospital Universiti Sains Malaysia (HUSM) in six months. Sample size were 128. Patients fulfill the inclusion criteria were included in this study. Results were documented in pre prepared data entry sheet. Results: 138 patient intubated during this study. Mean age of patient is 50.47 years. Majority were male , 95(68.84%). 94 case (68.12%) were due to non trauma case and 44 (31.88%) were trauma case. Most frequent indication ware airway at risk with percentage of 39% . Rapid sequence intubation (RSI) were the most frequent method of airway management 110 case (79.71%). Fentanyl was the commonest pretreatment agents used in 65.2% of case. For sedation, 26.6% of non trauma patients were given midazolam while for trauma, propofol were used. Most common paralytic agent given were succinylcholine, 72.5%. 98.55% were intubated successfully and only 2 cases (1.45%) failed intubation. 111 case intubated in single attempt (80.43%). 6 cases intubated with more then 3 attempts (4.35%). 9 cases (6.52%) noted to have difficult intubation and most common cause of difficult intubation were anterior cord position (44.4%). The most frequent intervention for difficult airway was by using bougie in 4 cases (44.4%). 57 case (43.3%) develop complication which were hypotension 49.1%, and cardiac arrest 33.3%. 2 factors showed significant association with successful intubation which were difficult airway and multiple attempts. Factor associated with difficult intubation were number of attempts during intubation and the presence of complication. Conclusion: Emergency department, Hospital Universiti Sains Malaysia (HUSM) have a very high success rate of intubation. The most common indications was airway at risk and common method of intubation done was rapid sequence intubation (RSI). Agent commonly use for pretreatment were fentanyl, while induction agent used were propofol and midazolam. For paralytic agent succinylcholine were used in most intubations. Complication rate were fairly high since due to most cases referred were severely or critically ill. There were low incidence of difficult intubation. Predictors of difficult intubations were multiple intubation attempts and development of complications.